PENERAPAN MODEL PEMBELAJARAN PROBING PROMPTING BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM SISWA KELAS VII MTS AL-IKHLAS PERANAP KABUPATEN INDRAGIRI HULU - Mona Riski Lestari; Sopiatun Nahwiyah; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
The problem of this research stems from the low learning outcomes. This is the background for researchers to conduct research using the Video media Assisted Probing Prompting learning model to improve learning outcomes in Islamic Cultural History subjects at MTs Al-Ikhlas Peranap class VII. The type of research used is Classroom Action Research (CAR) with qualitative descriptive methods, the subjects, of this research are class VII students of MTs Al-Ikhlas Peranap with a total of 33 students, the collection techniques used are observation, interviews. Instruments and documentation. The results showed that learning using the Probing Prompting Learning Model Assisted by Video Media could improve student learning outcomes, this was evident from the observations obtained in each cycle, in the Pre-cycle the percentage of student learning outcomes only reached 27,27% in Cycle I increased to 36,36%. and in Cycle II it increased to 81,81%, it can be concluded that the application of the Probing Prompting learning model assisted by Media Video which was carried out in Islamic Cultural History learning could improve the learning outcomes of class VII students of MTs Al-Ikhlas Peranap.